Congenital Absence of the Cruciate Ligaments - Smith, Derek B.; Amirault, J. David; Leahey, Lorne (DALHOUSIE MEDICAL JOURNAL, 2000)
Congenital absence of one or both cruciate ligaments is a rare event, and little literature exists regarding this abnormality.  Patients with this condition often have associated anomalies.  This study looked at 6 subjects with congenital abnormalities often associated with absence of the cruciate ligaments.  The subjects were followed by a questionnaire and knee examination.  This paper presents results of congenital absence of the cruciate ligaments on knee instability and activities of daily living.